PENINGKATAN KEMAMPUAN GURU DALAM MELAKSANAKAN PEMBELAJARAN DARING MENGGUNAKAN APLIKASI GOOGLE CLASSROOM DAN ZOOM MELALUI PENGARAHAN KONSEP DAN SUPERVISI KEPALA SEKOLAH DI SDN 2 RAGAWACANA TAHUN AJARAN 2020/2021 - Hermawan, Iwan (Jurnal Sains Indonesia, 2022)
This School Action Research is entitled "Improving Teacher Ability in Implementing Online Learning Using Google Classroom and Zoom Applications Through Concept Briefing and Supervision of Principals at SDN 2 Ragawacana for the 2020/2021 Academic Year". The aim is to improve the ability of teachers to use the Google Classroom and Zoom applications during online learning during the Covid-19 pandemic. This research method is school action research which is carried out in 2 cycles of improvement. The subjects of this study were all 9 teachers at SDN 2 Ragawacana consisting of 6 female teachers and 3 male teachers. Data collection techniques in this study were carried out through activities in the form of: (a) action planning; (b) the implementation of the action; (c) action observation; and (d) reflection. The results of the study show that the ability of teachers to use the Google Classroom and Zoom applications has increased in each cycle. From the average value of the teacher's ability of 75 in the 1st cycle of the 1st meeting, it increased to 77 in the 1st cycle of the second meeting. Then it increased back to 80 in cycle 2, meeting 1 and 84 in cycle 2, meeting 2 with an average value of cycle 1 of 76 and cycle 2 of 82. This shows that concept direction and supervision can improve the ability of SDN 2 Ragawacana teachers. in the use of Google Classroom and Zoom applications in the implementation of online learning during the Covid-19 pandemic.